PERILAKU PETANI SAYUR DALAM PEMANFAATAN PUPUK ORGANIK DI KAKASKASEN KOTA TOMOHON - Jesika Lumban Gaol; Ventje V. Rantung; Benu Olfie L.S (Sam Ratulangi University, 2016)
The purpose of this study was to determine the behavior of vegetable farmers in the use of organic fertilizers. Data used in this study is in the form of primary and secondary data. Primary data is data obtained from direct interviews with 30 respondents through the questionnaire that has been prepared. Sample collection method use purposive sampling. Secondary data is data obtained from the office of Kakaskasen Two Village. Data analysis was done using descriptive analysis. The finding of this reseach showed that vegetable farmers in the village of Kakaskasen Two are farmers who earn high incomes and have good behavior as vegetable growers.